Peran Dinas Pemberdayaan Masyarakat Dan Desa Dalam Meningkatkan Akuntabilitas Dan Transparansi Pengelolahan Keuangan Desa Di Kabupaten Sikka - Maria Oktavia Adriani; Yosefina Andia Dekrita; Maria Silvana Mariabel Carcia (Jurnal Projemen UNIPA, 2026)
This activity aimed to determine the role of the Community and Village Empowerment Office (DPMD) in improving accountability and transparency of village financial management in Sikka Regency. This activity was conducted at the DPMD of Sikka Regency using data collection method through direct observation, interviews, and documentation studies during the implementation of the activity. The results activity show that DPMD has an important role in improving accountability and transparency in village financial management through the implementation of training, guidance and supervision, evaluation and reporting, as well as problem handling. In addition, utilization of the Village Financial System application (SISKEUDES) has become one of the strategic efforts to support information openness and financial accountability of village finances. Nevertheless, several obstacles still exist, such as the limited understanding of village officials regarding village financial management. Therefore, it is necessary to improve the quality of training and supervision on a continuous basis so that vilage financial management will operate effectively, transparently, and accountably.